2016
DOI: 10.18632/oncotarget.9386
|View full text |Cite
|
Sign up to set email alerts
|

CXCL16 regulates cisplatin-induced acute kidney injury

Abstract: The pathogenesis of cisplatin-induced acute kidney injury (AKI) is characterized by tubular cell apoptosis and inflammation. However, the molecular mechanisms are not fully understood. We found that CXCL16 was induced in renal tubular epithelial cells in response to cisplatin-induced AKI. Therefore, we investigated whether CXCL16 played a role in cisplatin–induced tubular cell apoptosis and inflammation. Wild-type and CXCL16 knockout mice were administrated with vehicle or cisplatin at 20 mg/kg by intraperiton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…Previously, we reported that inflammatory cytokines have an important role in cisplatin-induced AKI. 22,23 Here we found that Nox4 overexpression increased the levels of cisplatin-induced inflammatory cytokines, including TNF-α, IL-1β and IL-6 mRNA levels, compared with the control group (Figure 5e). Thus these data indicate that Nox4 overexpression accelerates cisplatininduced AKI.…”
Section: Resultsmentioning
confidence: 67%
“…Previously, we reported that inflammatory cytokines have an important role in cisplatin-induced AKI. 22,23 Here we found that Nox4 overexpression increased the levels of cisplatin-induced inflammatory cytokines, including TNF-α, IL-1β and IL-6 mRNA levels, compared with the control group (Figure 5e). Thus these data indicate that Nox4 overexpression accelerates cisplatininduced AKI.…”
Section: Resultsmentioning
confidence: 67%
“…Substantial evidence has indicated that tubular cell apoptosis contributes to the pathogenesis of AKI, which plays an important role in renal fibrosis [18]. Therefore, we examined the effect of vehicle and TAK1 overexpression transfection treatment on apoptosis of renal tubular epithelial cell with sham or H/R treatment.…”
Section: Upregulation Of Tak1 Aggravates Apoptosis Of Renal Tubular Ementioning
confidence: 99%
“…Increasing evidence has indicated that tubular necrosis/apoptosis is an important mechanism underlying IR-induced AKI [ 17 , 18 ]. Therefore, we investigated tubular epithelial cell apoptosis induced by IR to confirm the success of the model.…”
Section: Resultsmentioning
confidence: 99%